2008
DOI: 10.1182/blood-2007-10-119743
|View full text |Cite
|
Sign up to set email alerts
|

EPO receptor circuits for primary erythroblast survival

Abstract: EPO functions primarily as an erythroblast survival factor, and its antiapoptotic actions have been proposed to involve predominantly PI3-kinase and BCL-X pathways. Presently, the nature of EPOregulated survival genes has been investigated through transcriptome analyses of highly responsive, primary bone marrow erythroblasts. Two proapoptotic factors, Bim and FoxO3a, were rapidly repressed not only via the wild-type EPOR, but also by PY-deficient knocked-in EPOR alleles. In parallel, Pim1 and Pim3 kinases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 75 publications
6
78
0
1
Order By: Relevance
“…These data suggest that the improved survival of EPO-treated erythroblasts was likely mediated by STAT5 signaling. 33 In this regard; the condition of mk/mk mice treated with EPO resembles that of β-thalassemia mice with dramatically elevated endogenous EPO and increased BCL-X L expression, which is responsible for the prevention of apoptosis of thalassemic erythroid cells in this model. 19 The possible involvement of any substantial increase in iron utilization by individual erythroid cells as a contributing factor to the positive effects of EPO therapy can be ruled out by the fact that the patients' erythrocyte characteristics (MCV and MCH) remained unchanged with EPO supplementation.…”
Section: Discussionmentioning
confidence: 90%
“…These data suggest that the improved survival of EPO-treated erythroblasts was likely mediated by STAT5 signaling. 33 In this regard; the condition of mk/mk mice treated with EPO resembles that of β-thalassemia mice with dramatically elevated endogenous EPO and increased BCL-X L expression, which is responsible for the prevention of apoptosis of thalassemic erythroid cells in this model. 19 The possible involvement of any substantial increase in iron utilization by individual erythroid cells as a contributing factor to the positive effects of EPO therapy can be ruled out by the fact that the patients' erythrocyte characteristics (MCV and MCH) remained unchanged with EPO supplementation.…”
Section: Discussionmentioning
confidence: 90%
“…55 However, studies using EpoR tyrosine-mutants demonstrated that PI3K/Akt activation is also indirectly mediated via Y343, involving the adaptor Gab2. 37,55,56 Stat5 and Akt pathways are thus coupled in EpoR signaling and might cooperate in target gene activation. Interestingly, we could show that KIT murine embryonic stem cells as previously described.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, anti-apoptotic Bcl2l1/Bcl-xL, Mcl1, Trib3 and pro-apoptotic Nix (coexpressed with Bcl-xL during erythroid maturation) were not upregulated in KIT D816V cells (Figures 4a and b, Supplementary Figure 4A). 21,[37][38][39][40] Alongside, downregulation of Bad and Bid was impaired (Figure 4a). These data show that continuous Kit signaling perturbs induction of the transcriptional program associated with terminal erythroid maturation and interferes with regulation of key mediators of cell cycle control, cell death and survival, thereby leading to continued proliferation and elevated apoptosis during terminal differentiation.…”
Section: Kitmentioning
confidence: 97%
“…In a similar manner, mammalian Tribs appear to regulate differentiation linked to cell division during (1) hematopoiesis (Lin et al, 2007;Eder et al, 2008;Sathyanarayana et al, 2008), (2) myogenesis (Kato and Du, 2007;Sung et al, 2007), (3) vascular smooth muscle formation (Chan et al, 2010), (4) lymphocyte differentiation (Selim et al, 2007), and (5) adipogenesis (described below).…”
Section: Adipocyte Differentiation and Hematopoiesis: Clues To Trib Rmentioning
confidence: 98%